2008
DOI: 10.1371/journal.pone.0003843
|View full text |Cite
|
Sign up to set email alerts
|

Sampling-Based Approaches to Improve Estimation of Mortality among Patient Dropouts: Experience from a Large PEPFAR-Funded Program in Western Kenya

Abstract: BackgroundMonitoring and evaluation (M&E) of HIV care and treatment programs is impacted by losses to follow-up (LTFU) in the patient population. The severity of this effect is undeniable but its extent unknown. Tracing all lost patients addresses this but census methods are not feasible in programs involving rapid scale-up of HIV treatment in the developing world. Sampling-based approaches and statistical adjustment are the only scaleable methods permitting accurate estimation of M&E indices.Methodology/Princ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
108
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(113 citation statements)
references
References 17 publications
(29 reference statements)
5
108
0
Order By: Relevance
“…Gaps in care, where a patient discontinued attending the clinic for some time but subsequently returned to care, were not considered as losses to follow-up. On the other hand, patients who were outreached were essentially treated as having been lost to follow-up regardless of the length of time between their last visit and the outreach encounter date as, once traced successfully, their loss to follow-up status would never be determined with certainty 17. This only applies to cohorts with documented outreach programmes (Kenya) or established linkages to vital registries (South Africa).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Gaps in care, where a patient discontinued attending the clinic for some time but subsequently returned to care, were not considered as losses to follow-up. On the other hand, patients who were outreached were essentially treated as having been lost to follow-up regardless of the length of time between their last visit and the outreach encounter date as, once traced successfully, their loss to follow-up status would never be determined with certainty 17. This only applies to cohorts with documented outreach programmes (Kenya) or established linkages to vital registries (South Africa).…”
Section: Methodsmentioning
confidence: 99%
“…17 For South African data, we used similar methods, but lost patients were instead ‘searched’ in the death registries of the country 28. Only passively determined death information was available in all other cohorts.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…death, transfer out) is unknown as LTFU contributes to inaccurate conclusions about the effectiveness of a given programme. 23,24 A 2009 systematic review and metaanalysis of 17 point-in-time ART LTFU studies concluded that only 63% of patients could be found to ascertain their vital status, and 46% of patients in African studies had died by the time they were traced. 19 Existing LTFU studies have been limited to retrospectively examining the true outcomes of an entire ART cohort at one point-in-time months or years after patients actually defaulted.…”
Section: Introductionmentioning
confidence: 99%